APLIKASI TONG SAMPAH OTOMATIS BERBASIS MIKROKONTROLER UNTUK MEMUDAHKAN PROSES PEMBUANGAN SAMPAH DI DESA BEDAHLAWAK KECAMATAN TEMBELANG - hanifah hanifah123; Iin Baroroh; Amin Yahya; Nami'atul Ma'arifah (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2022)
Every region must have some problems to save. Garbage, when it is not managed well, will cause some problems related to environment and health. Village Bedahlawak, located in Jombang, is one of villages facing this problem. There is garbage collection which is too overflowing because this waste is not taken regularly by the officials there and the way villagers collect the garbage is coming to the place where they have to open the big garbage can. Therefore, the villagers initiated to create a tool that is easy and efficient for waste disposal. Unfortunately, that project did not run well so that we initiated to create an automatic garbage can based on micro controller which functions to ease the waste disposal and make it more efficient with certain distances and they do not need to go to the place where they have to throw their waste and open the cover of dustbin. We create that device by assembling some tools that were bought. In assembling process, we involve villagers to actively participate in this agenda and know how to make it so that later they are able to assemble that device by themselves without our guidance. After the device is ready, we did the simulation and socialization related to how to use that device. It could be seen that the villagers were enthusiast to use that device.  Unfortunately, the tools that were used are too expensive for the villagers if they want to assemble it. Therefore, it is hoped that in the next research we can find or change some expensive tools to affordable tools so that the villagers can assemble that device by themselves or innovate it.